Plant Worlds - Heather I. Sullivan (Plant Perspectives)
Plant communities create and enable most of Earth’s living worlds by shaping ecological water and airflows, producing energy and matter through photosynthesis, and linking into vast, interconnected mycorrhizal fungal networks of communication to form interactive, multispecies, and distributive intelligences. We all live in various plant-formed worlds, an under-acknowledged fact in many extractivist cultures today. This essay briefly compares three works of science fiction featuring alien forest worlds that focus specifically on world-shaping vegetal power in which human or humanoid beings exist: Ursula K. Le Guin’s 1972 The Word for World is Forest, Alan Dean Foster’s 1975 Midworld and Marcus Hammerschitt’s 1998 German novel, Target. These three texts immerse the reader in alien forest worlds dominated by plants that human beings try to exploit with various forms of failure. From these explicit failures in otherworldly realms, we find narrative options for reimagining our relationships and resonances with our own powerful vegetal beings back on Earth.